Efficient Block Designs for Mixed Level Factorial Microarray Experiments based on Baseline Parameterization - Sukanta Dash; Rajender Parsad (Journal of the Indian Society of Agricultural Statistics, 2025)
A procedure of obtaining efficient block designs in block size 2 for n-factor mixed level factorial microarray experiments based on baseline parameterization has been given. A software module has been developed using C# programming language with ASP.NET platform for generation of efficient block designs in block size 2 for n s s s × × × and n denotes the number of factors and j j v== factorial experiments in 1 v arrays, where j denotes the number of levels of jth factor , the total number of treatment combinations. For n = 2, the software developed can also generate efficient block designs for 1 2 1 1 1 1 ( ) ( )( ) v b v s s , where b is the number of arrays.